Collaborative Planning Between Village Governments, Investors, and Communities as a Solution to MSME Development Problems (Case Study in Cimarias Village, Pamulihan District, Sumedang Regency) - Heru Rochmansjah (Institute of Computer Science (IOCS), 2021)
Collaboration is working together, especially to combine ideas. This follows the definition of collaboration, namely, as a network or distribution of information, resources, activities, and organizational capabilities in two or more sectors to achieve goals that cannot be achieved if working alone. This type of research is qualitative research with an analytical-descriptive approach. Collaborative planning between the village government and the community regarding the empowerment of MSMEs originating from the Cimarias Village Fund Allocation and funds from investors. The data collected comes from the results of interviews and observations consisting of primary data and secondary data. From the research results, it can be seen that the development of MSMEs carried out by the Cimarias village government consists of several things, namely: 1) Training for MSME actors; 2) Exhibition of agricultural products; 3) Provision of capital in the form of equipment, and 4) issuance of business regulatory licenses; and 5) Providing capital for small business actors.